Hip dips technique: Filling lateral depressions with hyaluronic acid of large particles - Luciana Lourenco; Helena Medeiros; Luísa Ferreira; Natasha Favoretto Dias de Oliveira; Roberta Lopes; Rosa Sigrist (Wiley, 2024)
Abstract Introduction Hip dips, often referred to as the pronounced trochanteric depression, can be caused by athletic muscular definition or the ageing process. This depression might impact the desirable contour of the buttocks in some female patients. Patients and Methods A technique is described for female patients exhibiting moderate to severe degrees of lateral trochanteric depression. This technique utilizes a specific marking, a well‐thought‐out plan and a designated product. Eleven patients were selected to use this technique to improve their trochanteric depression and enhance their buttocks contour without undergoing surgery. The product used was Sofiderm Subskin, which was applied at the intermediate subcutaneous layer. Results The authors report favourable aesthetic results with the proposed technique, and the patients expressed high satisfaction levels. Discussion Though safe for injection, the lateral gluteal depression can still be challenging to expand. The product chosen has both a high G prime and a large molecular size, contributing to its resistance to deformation. Conclusion The hip dips technique using hyaluronic acid for the augmentation of lateral depression has shown to be minimally invasive; it provides quick results without significant risks or downtime.